2001
DOI: 10.1016/s0896-6273(01)00296-3
|View full text |Cite
|
Sign up to set email alerts
|

Contactin Orchestrates Assembly of the Septate-like Junctions at the Paranode in Myelinated Peripheral Nerve

Abstract: Rapid nerve impulse conduction depends on specialized membrane domains in myelinated nerve, the node of Ranvier, the paranode, and the myelinated internodal region. We report that GPI-linked contactin enables the formation of the paranodal septate-like axo-glial junctions in myelinated peripheral nerve. Contactin clusters at the paranodal axolemma during Schwann cell myelination. Ablation of contactin in mutant mice disrupts junctional attachment at the paranode and reduces nerve conduction velocity 3-fold. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
501
4
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 477 publications
(541 citation statements)
references
References 49 publications
25
501
4
9
Order By: Relevance
“…The proteins in the PJB that link the loop membranes with the axolemma form a complex of heterodimers consisting of neurofascin 155 and caspr/paranodin (Boyle et al, 2001;Poliak et al, 2001;Scherer and Arroyo, 2002;Tait et al, 2000). In a unique heterologous handshake, the glial cell contributes neurofascin 155 and the neuronal cell provides caspr.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteins in the PJB that link the loop membranes with the axolemma form a complex of heterodimers consisting of neurofascin 155 and caspr/paranodin (Boyle et al, 2001;Poliak et al, 2001;Scherer and Arroyo, 2002;Tait et al, 2000). In a unique heterologous handshake, the glial cell contributes neurofascin 155 and the neuronal cell provides caspr.…”
Section: Introductionmentioning
confidence: 99%
“…Contactin, residing in the axonal membrane, brings the other proteins to the handshake. Deficiency in either caspr, contactin, or neurofascin 155 produces a disorganization of the paranodal loops and a reduction in axon conduction velocity (Bhat et al, 2001;Bonnon et al, 2007;Boyle et al, 2001;Sherman et al, 2005). At the nodal/paranodal region in the myelinated axons of sciatic nerves of mice deficient in caspr, PJBs were missing and abnormal, swollen mitochondria were observed (Einheber et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 F3 is the first GPI-linked molecule identified that is located in both nodal and paranodal regions. 15,16 It forms an intracellular complex with paranodin, a single transmembrane protein 17 also termed Caspr and modulates its transfer from the endomembrane system to the axolemma. 15,18 F3 also is clustered at the paranode, a critical site of axoglial dialog for initiating myelination, from the first postnatal week.…”
Section: Discussionmentioning
confidence: 99%
“…Ce sont des molécules qui ont été impliquées dans l'adhérence entre les cellules ou entre les cellules et la matrice extracellulaire. L'étude de modèles animaux murins, dont les gènes codant pour la paranodine/Caspr ou la contactine/F3 -les protéines axonales des familles NCP et IgSF-CAM, respectivement, présentes au niveau des paranoeuds -ont été invalidés, montre que ces deux protéines sont essentielles pour la formation des jonctions de type « septé » [25,26]. Une perturbation de ces jonctions a, par ailleurs, été observée chez d'autres souris mutantes [27][28][29].…”
Section: Interactions Axo-glialesunclassified